PENERAPAN MODEL PEMBELAJARAN INVITATION INTO INQUIRY PADA MATA PELAJARAN KKPI KELAS X1 ADMINISTRASI PERKANTORAN SMK N 1 BATANG TAHUN 2016 - Nikmah, novliansari; Isdiyarto, Isdiyarto; Prastyanto, Dhidik (Edu Komputika Journal, 2017)
The implementation of the 2013 curriculum  at SMK N 1 Batang need for new learning models that correspond to the curriculum. This study aims to determine whether there is any difference in student learning outcomes using models invitation into inquiry and student using expository models on the subjects of  KKPI class XI AP SMK N 1 Batang. The design was nonequivalent control group pretest-posttest design. Average values obtained experimental class 82 703, the control class 74.71. The results of t-test t = 11.863 while t table = 1.99. So thitung> ttable, means there are significant differences between the two groups. It can be concluded that the application of the invitation into inquiry learning model is better than the application of expository teaching model on the subjects of KKPI class XI AP SMK N 1 Batang. Suggested invitation into inquiry learning model can be applied to subjects KKPI with different competencies that learners learning outcomes can reach over KKM predetermined value. _________________________________________________